Indocyanine green mediated antimicrobial photodynamic therapy: A non-invasive treatment approach for chronic periodontitis with type 2 diabetes mellitus: A randomized controlled clinical trial - Priyanka Agarwal; Pratibha Shashikumar; Rakshitha S (Journal of Oral Biology and Craniofacial Research)
Background: Periodontitis is a destructive chronic inflammatory disorder of the periodontium and is a major cause of loss of teeth. Uncontrolled diabetes affects periodontal status and chronic periodontitis affects the glycemic status. Nonsurgical periodontal therapy is often not sufficient in completely eliminating the pathogens. Hence antimicrobial photodynamic therapy (aPDT), is being used in medically compromised patients as it does not cause adverse effects that are seen with other adjunctive treatments. This study aimed to evaluate the efficacy of antimicrobial photodynamic therapy using Indocyanine green as an adjunct to scaling and root planing in the treatment of periodontitis in controlled Type 2 Diabetes Mellitus (DM) patients with chronic generalized periodontitis. The objective to see improvements in clinical parameters and microbiological parameters along with its effect on glycemic levels. Materials and methods: In this randomized controlled clinical trial a total of 40 chronic periodontitis patients with Type 2 DM were randomly assigned into test and control groups of 18 participants each. The test group received.Scaling and root planing (SRP) + aPDT) while the control group received only SRP. In SRP + aPDT group, pockets were irradiated with a diode laser after irrigation with Indocyanine green. Assessment of clinical parameters like plaque index (PI), gingival index (GI), probing depth, (PD), clinical attachment level (CAL), and glycated haemoglobin (HbA1c), as well as microbiological analysis for Porphyromonas gingivalis (Pg) and Aggregatibacter actinomycetem comitans (Aa) was done at baseline & 3 months post-therapy and data were statistically analysed. Results: aPDT as an adjunct to SRP improved clinical and microbiological parameters. A statistically significant difference (p < 0.001) was noted on intergroup comparison with respect to PD, CAL, and colony forming units (CFU/ml) of Pg and Aa. There was an improvement in HbA1c levels from baseline to 3 months in both the groups however, there was no significant difference between the groups at 3 months. Conclusion: The use of Indocyanine green mediated aPDT as adjuvant therapy in treatment of chronic periodontitis in Type 2 diabetes mellitus patients resulted in significant reduction in microbial counts as well as rendered additional clinical benefits. Clinical significance: aPDT as adjunctive therapy to SRP can be a non-invasive treatment of choice for chronic periodontitis in medically compromised patients like Type 2 Diabetes mellitus patients.